The Cuckoo's Calling - Galbraith, Robert (New York : Mulholland Books/Little, Brown and Company, 2018)
When a troubled supermodel falls to her death from the balcony of her London home, it is assumed that she committed suicide. However, her brother has his doubts and calls in private detective Cormoran Strike to investigate. Strike is a war veteran--wounded both physically and psychologically--and his private life is in disarray. The case gives him a financial lifeline, but it comes at a personal cost: the more he delves into the young model's world, the darker things get and the closer he comes to danger
Keywords: Private investigators -- England -- London -- Fiction; Afghan War, 2001- -- Veterans -- Fiction; Murder -- Investigation -- Fiction; Detective and mystery stories; Mystery fiction